Viral Marketing dan Motivasi Wisatawan dalam Meningkatkan Minat Berkunjung pada Destinasi Wisata di Kabupaten Bima - Sri Ernawati (Jurnal Maksipreneur, 2020)
Tourism is one of the new style industries, so it needs special attention. The tourism industry can provide rapid economic growth in terms of employment opportunities, income, the standard of living, and inactivating other production sectors. This study aims to analyze and test the effects of viral marketing and tourist motivation both partially and simultaneously in increasing interest in visiting tourist destinations in Bima District, Nusa Tenggara Barat, Indonesia. This research used quantitative methods by distributing questionnaires to 96 people who had visited tourism destinations in Bima District. The questionnaires would be tested for validity and reliability first, and then processed with SPSS version 20.0. Data analysis in this research used multiple linear regression methods with SPSS (Statistical Package for the Social Sciences) 20.0. The results showed that viral marketing and tourist motivation have an effect on tourism destinations and it will positively influence the visiting interest to Bima District, respectively. Simultaneously, viral marketing and tourist motivation can raise visiting interest in Bima District’s tourism destinations.